The Influence of Budget Accuracy, Clarity of Budget Targets, and Managerial Control on Performance Accountability - Krisna Vita Rosalinda; Tituk Diah Widajantie (Profesional Muda Cendekia Publishing, 2021)
This study aims to examine and analyze the effect of budget accuracy, clarity of budget targets and managerial control on performance accountability in Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya.. The endogenous variable used is performance accountability. The sample of this research is all employees who work in Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya the field of budget and treasury accounting. The selection of the sample technique uses purposive sampling with the data collection method used is the survey method and distributes questionnaires with a total of 52 respondents. The collected data were analyzed using Partial Least Square (PLS) analysis technique with SmartPLS 3.0 software. The results of this study indicate that (1) budget accuracy has an effect on performance accountability in Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya. (2) Clarity of budget targets has no effect on performance accountability in Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya. (3) managerial control effect on performance accountability in Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya.